Evaluation of indoor environmental quality conditions in secondary schools' classrooms in Sharjah - AL ANSARI, ASMA (2018)
Good Indoor Environmental Quality (IEQ) is essential to enhance better productivity and performance of teachers and students. Research was conducted at four selected schools in residential areas of Sharjah. The schools were selected according to building age and gender differences in order to investigate the influence of indoor environment condition on student’s health and performance. The IAQ, light and sound levels have been determined by using questionnaire and automatic portable devices. The result show the IEQ factors in all schools were either below or above the recommended level suggested by Dubai municipality and ASHRAE, these factors includes the following: concentration level of CO2 indoor air temperature, ventilation, humidity, artificial and natural light and acoustic conditions. The indoor environmental conditions were similar in all four schools. Results show that poor IEQ can increase the risk of sick building syndrome and affect student’s health and productivity. Results also show that female students are more sensitive to poor IEQ as compared to male students.